Facing The World in Vietnam: Feedback From Trainees on the Educational Value of Surgical Missions to Help Patients With Craniofacial Deformities. Issue 7 (October 2016) - Richardson, Charlotte; Hachach-Haram, Nadine; Billingsley, Michael; Timoney, Norma; Grant, Will; Gerarchi, Paul; Collier, Jonathon; Eccles, Simon; Young, Richard; Kirkpatrick, Niall
Abstract : Background: Education and training of local healthcare staff is a crucial component of a surgical mission. Facing The World (FTW) is a UK-based craniofacial charity that provides facial reconstructive surgery to children with complex, craniofacial anomalies. As part of its global initiative, FTW has developed a training outreach program in Vietnam. The aim of this study was to analyze feedback data to evaluate the educational value of the training program and identify areas for improvement. Methods: Feedback was obtained through both 5-point Likert scale and open-ended response questions on written questionnaires. Six postmission reports were reviewed, and used as a base for the content of the questionnaires. Selective sampling was used, with questionnaires distributed to all Vietnamese and UK trainees who have been part of the FTW training program. Results: Seven Vietnamese trainee questionnaires were completed, a response rate of 87.5%. Twelve UK trainees completed the feedback questionnaire, giving a response rate of 85.7%. One hundred percent of local trainees and 83.3% of UK trainees found the training program to be useful or very useful, with no trainees deeming the training program not useful or of no use at all. Conclusion: The training missions offered by FTW have successfully provided education to both UK and Vietnamese surgeons in Craniofacial surgical techniques and patient care. No negative responses were identified in both questionnaires. The feedback provides evidence of FTW's effective training program, while allowing insight into where further improvements can be made.